Health and educational achievement of school-aged children: The impact of anaemia and iron status on learning - Thando P. Gwetu; Myra Taylor; Meera Chhagan; Murray Craib; Shuaib Kauchali (AOSIS, 2019)
Background: Anaemia is a common blood disorder in children and is known to cause complications such as lethargy and stress on bodily organs. Children from disadvantaged communities often fail to achieve their age-related potential with iron deficiency anaemia stated as a risk factor through causing inattentiveness and learning problems. Limited evidence exists for the adverse effects of iron deficiency anaemia on the developing child's brain from South African studies. Aim: The objective of this study was to determine the local prevalence of anaemia and iron deficiency and to examine their association with psychomotor development and school performance in school-aged children. Setting: This study was conducted in a peri-urban disadvantaged community from KwaZulu-Natal, South Africa. Methods: Children aged 6 to 8 years from KwaZulu-Natal were enrolled (n = 184). Three parameters of assessment were used: clinical data, biochemical data (haemoglobin levels and iron studies) and school performance (interviews with caregivers, teachers and the children). Anaemia presence and iron deficiency were the hypothesised mediating variables through which growth, development and school performance were influenced. Results: A high point prevalence of anaemia (23.4%), iron deficiency anaemia (4.9%) and helminth infection (27.1%) was identified. Impaired cognitive assessment scores (20.7%) were prevalent in the children sampled. Behavioural problems (4.3%), poor memory function (4.3%) and impaired attention (1.1%) were of low prevalence. Anaemia and iron deficiency were both associated with impaired fine motor skills (p < 0.05). Anaemia was significantly associated with low cognitive scores (p = 0.01). Neither anaemia, iron status nor helminth infection significantly predicted school performance in the children sampled. Conclusions: The point prevalence of anaemia and iron deficiency among the sampled children was higher than the national prevalence. The sample size was however inadequate for drawing statistical conclusions about psychomotor development and school performance because of the low prevalence of the different outcomes that were examined. Practical challenges faced in conducting this investigation in rural South African schools were discussed.